Application of Genetic Algorithms for Multiple Traveling Salesman Problems: A Case Study of Distribution of Sacrificial Animal Meat at the Islamic Center in Mataram City - Alqorni, Wais; Prahara, Adhi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
Islamic Center of Mataram is the center of Islamic religious activities. On Eid al-Adha and Tasyrik Day, animals are slaughtered. The average amount of animal meat that will be distributed annually is 7500 Kg of raw meat where will be distributed to 9 (nine) urban villages in Mataram City. In distributing the meat of the sacrificial animal, they only have limited time and staff, which is only done on 3 days of Tasyrik or sometimes only 2 days because the slaughtering is not carried out immediately after Eid prayer. Distribution starts from 12.00 - 16.00 every day. To help the problem of the distribution process, known as the Multiple Traveling Salesman Problem, the author uses a genetic algorithm to solve the problem. To build a software to implement Genetic Algorithm on the M-TSP problem in the distribution of sacrificial animal meat, several stages are carried out, starting from collecting data used to apply genetic algorithms, designing display prototypes and features to be able to process the data that has been collected, stages of system coding become a web-based system and finally testing the system that has been made. By implementing officer data and distribution locations which will then be tested using one of algorithms, namely the Genetic Algorithm. The accuracy and efficiency of the total distance that will be taken in making a distribution route using this algorithm where calculation is carried out by finding the largest fitness value from several kromosomal populations that are generated after going through crossover process and gene mutations on each kromosome. The result from this system tests with different method are 100% from using a black box, and 81.7 from using SUS testing which is classified as good. The best average fitness value resulting from testing the distribution system of sacrificial animal meat using the number of chromosomes 9 as many as 5 experiments using the number of generations 3, and the crossover parameter = 40% and mutation = 40% which is 0.045 with a total distance of 22.33 km. The design of this system is very useful for the administrators Islamic Center of Mataram ta'mir as a reference in determining optimal route in process of distributing sacrificial animal meat as well as for authors in applying the scientific theory they have.